Polymorphisms in the +252(A/G) lymphotoxin-alpha and the -308(A/G) tumor necrosis factor-alpha genes and susceptibility to chronic periodontitis in a Czech population - Fassmann, Antonin; Holla, Lydie Izakovicova; Buckova, Dana; Vasku, Anna; Znojil, Vladimir; Vanek, Jiri (Journal of periodontal research, 2003)
BACKGROUND: Periodontitis is an inflammatory disease that leads to irreversible attachment loss, bone destruction and eventually tooth loss. Tumor necrosis factor (TNF), a pluripotent proinflammatory cytokine that is able to induce tissue destruction and bone resorption, has been implicated in the pathogenesis of periodontal disease. METHODS: In this study, we investigated an association between chronic periodontitis and two previously described bi-allelic polymorphisms in the TNF locus: a G to A transition at position -308 in the 5'promoter region of the TNF-alpha gene and an NcoI restriction fragment length polymorphism (RFLP) in the first intron (position +252A/G) of the lymphotoxin alpha (LT-alpha) gene. Genomic DNA was obtained from 132 patients with chronic periodontitis together with 114 age- and gender-matched unrelated control subjects. RESULTS: The TNF-alpha (-308G/A) polymorphism itself showed no association with chronic periodontitis, whereas the frequency distribution of the LT-alpha (+252A/G) genotypes showed statistically significant differences between patients and the reference group. The proportion of individuals carrying the LT-alpha 1/1 genotype was significantly lower in the group of patients with chronic periodontitis (0.8%) than in the control group (8.8%) (P < 0.0094, Pcorr < 0.05). However, the significant differences in the frequencies of the combined genotypes (TNF-alpha and LT-alpha) between the control and the patient groups were found using a simulation by applying the Monte-Carlo method (P < 0.01). CONCLUSION: Our data suggest that combined genotypes composed of the TNF-alpha and LT-alpha gene polymorphisms may influence the susceptibility to chronic periodontitis. We also showed that, comparing the two genes, the 1/1 genotype of the NcoI polymorphism in the first intron of the LT-alpha gene is a more informative marker and it may be one of the protective genetic factors against chronic periodontitis in our population.
Keywords: Guanine; Adenine; metoda Monte Carlo; Humans; Promoter Regions, Genetic; Case-Control Studies; guanin; lidé středního věku; lymfotoxin-alfa; běloši; polymorfismus genetický; studie případů a kontrol; Chronic Disease; Female; dospělí; frekvence genu; White People; Genotype; lidé; Periodontitis; Polymorphism, Genetic; Monte Carlo Method; TNF-alfa; Adult; adenin; ženské pohlaví; Male; Middle Aged; parodontitida; chronická nemoc; Genetic Predisposition to Disease; genetická predispozice k nemoci; Czech Republic; Gene Frequency; Introns; Tumor Necrosis Factor-alpha; genotyp; Česká republika; mužské pohlaví; introny; promotorové oblasti (genetika); Lymphotoxin-alpha